Kontribusi Muslim Minoritas dalam Menggulingkan Rezim Apartheid Di Afrika Selatan (1948-1994) - Afik Fathur Rohman (JSI: Jurnal Sejarah Islam, 2022)
This thesis aims to describe and analyze: (1) The history of the emergence of apartheid politics in South Africa, and (2) The contribution of Muslims in opposing the apartheid regime in South Africa with the period 1948-1994. This type of research focuses on library reseach. Some of the steps used in researching the object of study are heuristics, verification, interpretation, and historiography or what is often referred to as historical research methodology. The results of this study show that: First, apartheid politics officially lasted for forty-two years (1948-1990). This is against the backdrop of a white group that feels that it is superior to the black group that is seen as slaves, servants. Apartheid, which means separation, was formed with the aim of maintaining the purity of his race, so that to realize it Malan who won the 1948 elections made a kind of political policy strategy that later developed into discrimination against blacks. Second, The policy of implementing apartheid politics that oppresses many blacks, including Muslims, triggers resistance and resistance to the political policies implemented. This movement was realized by a series of Muslim organizations, such as CMYM, CMYA, Al-Qibla and The Call of Islam that strongly opposed the practice of oppression of apartheid regimes. The foundation of thinking used in this study refers to Max Weber's theory of social action.